Assessment of Ecological Sustainability for International Bays in the Context of Common Prosperity—A Case Study of Sanmen Bay in Zhejiang Province - Liu, Li; Zhang, Xiujuan; Chen, Zheqi; Zhou, Hailang; Li, Chao; Chen, Yujun (Frontiers in Environmental Science, 2022)
In this paper, the spatial distribution maps of Sanmen Bay’s landscape genres between 1995 and 2020 were drawn based on spectra, GPS data, and the genres’ information extracted through remote-sensing imagery, in a way to fundamentally evaluate the region’s coupling and coordinated development. Moreover, to provide a science-based reference point for protecting and utilizing the Bay’s wetlands, changes of landscape genres were examined through a transition matrix, and the drivers of these dynamics were analyzed on a Logistic regression model. In addition, a theoretical and appraisal system compatible with the comprehensive evaluation of a bay’s ecosystem was built upon the analysis of Sanmen Bay’s land and sea areas. This would provide a scientific basis for bay ecosystem preservation by complementing the theoretical architecture of comprehensively evaluating a bay’s environment and keeping the evaluation more timely and complete. Beyond that, we investigated the region’s social development and its spatial improvement over the marine economy from the perspective of a bay’s coupled society-economy-ecology system, which took into account manifest and latent environmental factors that have been absent in conventional bay development planning. Finally, through empirical analysis, to improve the social and economic landscape of Sanmen Bay provides effective policy recommendations, the study also made new efforts to explore and promote the sustainability of China’s Gulf ecosystem.